SURAT PERNYATAAN PENGUASAAN FISIK BIDANG TANAH SEBAGAI DASAR PENDAFTARAN TANAH SISTEMATIS LENGKAP (STUDI DI KECAMATAN CENGKARENG): Statement Letter of Physical Control of a Land Parcel as the Basis for Complete Systematic Land Registration (Case Study in Cengkareng District) - Sudi Hasby As Shidiqie; Novina Sri Indiraharti (Faculty of Law, Universitas Trisakti, 2025)
The implementation of the Complete Systematic Land Registration (PTSL) using the Statement of Physical Land Possession (SPPFBT) in West Jakarta still faces several challenges, particularly due to its weak legal standing. SPPFBT serves merely as a supplementary document without strong evidentiary value. This study raises two main issues: whether the use of SPPFBT in the PTSL program in Cengkareng District aligns with applicable laws and regulations, and what legal obstacles arise from its use. This research applies a normative legal method with a synchronization approach, descriptive in nature, relying on secondary data. The analysis is conducted qualitatively, with conclusions drawn deductively. The result and conclusion reveal that the principle of contradictory delimitation has not been optimally implemented, as is the case with the collection of physical and juridical data. SPPFBT lacks sufficient legal force, functioning only as an indicative document. The change in PTSL announcement period from 30 days to 14 days affects the program’s legal certainty and effectiveness. Out of 10,507 registered land parcels, 573 certificates could not be issued. In Cengkareng, the PTSL process remains problematic due to weak verification of SPPFBT, low public understanding, and inconsistent procedures in implementation.